THE ROLE MANAGEMENT AND PERFORMANCE ASSESSMENT INN DEVELOPMENT OF HUMAN RESOURCE AND INN INCOMES OF THE ORGANIZATION - Driton Fetahu (European Scientific Journal, ESJ, 2013)
As a result of changes in human resources approach new forms of Human Resources Management were created, that require increased commitment in human resources in order to achieve the highest possible results in an organization. As the technology advances greatly, there is continues need for investment in human resources in order to keep up in professional career development and revenues. Such results of human resources results are achieved through the application of positive methods and implementation of continuous education, as a demand and necessity of the global economy or new economy.One of the main roles of human resources is their action as a factor of change, transformation and as the decisive factor in the establishment and development of the organization.The purpose of this paper is to analyze the impact of human resources performance and new perspectives on human resource management in public organizations, in order to promote competition in the organization and beyond.This study will treat the impact of performance evaluation and new perspective aspect in the development of the human resources, identifying human potential in the organization and advance their career with the purpose of further organization development, revenues increase and economic growth of the organization.Topics of study research may be of a particular importance for staff who wishes to make changes or to analyze the impact of performance and motivation in the individual and organizational development.